2014
DOI: 10.12945/j.aorta.2014.14-004
|View full text |Cite
|
Sign up to set email alerts
|

Acute Conditions Caused by Infectious Aortitis

Abstract: Infection of the aorta is rare but potentially very dangerous. Under normal circumstances the aorta is very resistant to infections. Following some afflictions, the infection can pass to the aorta from blood or the surrounding tissues. The authors present their 5-year experience with therapy of various types of infections of the abdominal aorta. Methods: In the 5-year period between January 2008 and December 2012, the Surgical Clinic of the University Hospital in Pilsen treated 17 patients with acute infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Infected aortic aneurysms are rare, accounting for less than 3% of all aneurysms; most commonly caused by Salmonella species or Staphylococcus aureus . Other causes of aortitis include Escherichia coli, Kliebsella pneumoniae, Streptococcus sp., Candida sp., Aspergillus sp., and Listeria monocytogenes . The hallmark of aortitis due to C. septicum is the presence of periaortic gas as reported in 92.6% of cases .…”
Section: Discussionmentioning
confidence: 99%
“…Infected aortic aneurysms are rare, accounting for less than 3% of all aneurysms; most commonly caused by Salmonella species or Staphylococcus aureus . Other causes of aortitis include Escherichia coli, Kliebsella pneumoniae, Streptococcus sp., Candida sp., Aspergillus sp., and Listeria monocytogenes . The hallmark of aortitis due to C. septicum is the presence of periaortic gas as reported in 92.6% of cases .…”
Section: Discussionmentioning
confidence: 99%
“…Our patient's aortic arch infection was secondary to S. aureus. Although Salmonella aortitis is a well-recognized entity, particularly in the descending and abdominal aorta, 5 infections isolated to the aortic arch tend to have a more varied microbiologic etiology. In a review of nine patients with infected distal arch aneurysms, Okada and associates found S. aureus as the inciting pathogen in two cases, with a myriad of different organisms (all non-Salmonella species) identified in the other cases.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the most common bacterial organisms that cause infectious aortic aneurysms are Staphylococcus aureus and Salmonella species. Streptococcus, Pseudomonas, Candida, Cryptococcus, Aspergillus, and Mycobacterium tuberculosis are other sources of infection [ 4 ]. Aortic infections from K. pneumoniae are rare; the few cases of infectious aortic aneurysm caused by K. pneumoniae are mostly reported from eastern Asia, including Japan and Taiwan [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…K. pneumoniae is a gram-negative encapsulated rod. Gram-negative bacteria, including K. pneumoniae , have a higher tendency to expand and rupture the aortic wall than gram-positive bacteria [ 4 ]. K. pneumoniae is generally seen in patients with pneumonia, skin or soft tissue infection, or urinary tract infection.…”
Section: Discussionmentioning
confidence: 99%